2011
DOI: 10.4103/0970-0218.91418
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of overweight and obesity in affluent adolescent in Surat city, South Gujarat region, India

Abstract: Background:Obesity is a major global burden. Low levels of physical activity, TV watching, and dietary pattern are modifiable risk factors for overweight and obesity in adolescent.Objective:The objective of this study was to determine risk factors for overweight and obesity among affluent adolescent, in Surat city in south Gujarat.Design:Cross sectional from July 2009 to April 2010.Setting:Two private schools with tuition fees more than Rs. 2000 per month, were selected randomly using a random table.Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
49
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 17 publications
15
49
1
1
Order By: Relevance
“…2 A closer look at inappropriate dietary practices reveal increased snacking, intake of high calorie density foods, larger portion sizes, foods of poor nutritional quality as main culprits for emerging epidemic of childhood obesity in developing countries. 2,19,20,24 We also observed that obese children in our study were less active and were making unhealthy food choices by consuming fast food and carbonated drinks more often, a finding which is shared by other investigators as well. 20,24 Improved food product labelling with more nutritional information on product packaging (ex: traffic light and tea-spoon labelling for sugar, salt and fat content) would serve as a preventive strategy to address the serious public health concern of childhood obesity and help parents making healthier choices for their children as reported by Moretto et al 25 Low physical activity has been reported as significant risk factor for obesity by many investigators.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…2 A closer look at inappropriate dietary practices reveal increased snacking, intake of high calorie density foods, larger portion sizes, foods of poor nutritional quality as main culprits for emerging epidemic of childhood obesity in developing countries. 2,19,20,24 We also observed that obese children in our study were less active and were making unhealthy food choices by consuming fast food and carbonated drinks more often, a finding which is shared by other investigators as well. 20,24 Improved food product labelling with more nutritional information on product packaging (ex: traffic light and tea-spoon labelling for sugar, salt and fat content) would serve as a preventive strategy to address the serious public health concern of childhood obesity and help parents making healthier choices for their children as reported by Moretto et al 25 Low physical activity has been reported as significant risk factor for obesity by many investigators.…”
supporting
confidence: 73%
“…18 A number of studies conducted in recent years across various regions of India revealed higher prevalence of overweight and obesity among adolescents, particularly among females. [19][20][21] It is a known fact that adolescent females are physiologically programmed to the deposition of extra adipose tissues due to effect of the hormones during puberty. This to some extent explains relative preponderance of overweight and obesity among females.…”
mentioning
confidence: 99%
“…8 A study in Surat City however found a preponderance of females 70.4% than males 29.6% reportedly because one exclusive girls' school was included in the study. 9 In the present study, the proportion of government and private school distribution is also similar 33.8% and 34.0%. Similarly the distribution of government and private college is similar16.1%.…”
Section: Discussionsupporting
confidence: 50%
“…9 A review of a few select studies during 2001 to 2012 showed a prevalence of overweight among children aged 10-19 years to be 9.9 to 19.9 per cent; high in both boys (3 to 15.1%) than in girls (5.3 to 13.3%) indicating early onset of obesity affecting more of urban school adolescents (3.4 to 6.5%) as compared to 0.6 per cent among the rural adolescents with significant gender variations. [10][11][12][13][14][15][16][17][18] Vohra R et al 19 in 2011 in Lucknow found the prevalence of overweight and obesity was 17% and 0.73% respectively among school-going children. Important correlates were children playing out-door's games for less than 30 minutes and those consuming fast food.…”
Section: Discussionmentioning
confidence: 99%